Lärarutbildningen och miljonprogrammets skola - Niclas Månsson; Ali Osman (Educare)
In this article we examine two different but interconnected problems, which weaken the struggle for and the idea of equal education in the Swedish comprehensive educational system. One of the problems is the increasing segregation of the Swedish comprehensive school. This segregation is characterized socio, cultural and economic difference. In these areas the concentration of children with diverse ethnicity and low income background are high, while in other areas the opposite is true. In this article we focus on the former schools. These schools are characterized as low achieving schools, and schools that are in crisis. The second issue that is intimately connected to the low achieving school that we examine is the disposition and to some extent the composition of the teaching force. We argue that there is a disconnection between the two aspects, and ground the problem in teacher training. We argue that the current teacher education is not constructed to prepare teachers to meet the challenges in multiethnic schools located in socio-economic deprived areas. The article ends with a critical discussion of “low performing school” and the role of teacher education in preparing teachers for schools in segregated areas.